EXPLORING THE MECHANISMS OF WOUND HEALING PROPERTIES IN PLANTS: A COMPREHENSIVE REVIEW - Ishan Sharma; Shweta Durvasha (International Scientific and Current Research Conferences, 2023)
Wound healing is a complex process that involves various cellular and molecular mechanisms. Traditional medicine has utilized plants for centuries to promote wound healing. In recent years, modern science has confirmed the efficacy of various plant species in wound healing. This review provides a comprehensive overview of the mechanisms by which plants promote wound healing. We discuss the role of plants in each stage of wound healing, including hemostasis, inflammation, proliferation, and remodeling. We also explore the specific bioactive compounds found in plants and their mechanisms of action. Finally, we examine the potential of plant-based wound healing therapies in clinical settings.